The strategic importance of the Straits of Malacca for world trade and regional development - Hans-Dieter Evers; Solvay Gerke (University of Bonn, Center for Development Research (ZEF), 2006)
The Straits of Malacca are of strategic importance for world trade and regional development. They are vulnerable to social, political and natural disasters, but also bear great opportunities for economic and social development. Most of European trade with China and Japan is shipped through the Straits of Malacca. Most of the energy requirements of Japan depend on oil shipments from the golf states through the Straits of Malacca. The Straits have for centuries connected the Indian subcontinent with East and Southeast Asia as well as Europe with China as an alternative to the Northern 'Silk Road'. The states bordering the Straits, Indonesia, Thailand, Malaysia and Singapore form the core of the ASEAN region, one of the growth poles of the developing world. The areas bordering the Straits are themselves rich in natural resources from fisheries, to mangrove swamps and rain forests, from tin mining to gas and oil fields, but also beset by problems of tidal destruction (Tsunami), pollution through shipping and industries. The Straits are beset by problems of poverty, cross straits illegal migration and depletion of its natural resources. The very political stability of the Straits region is at stake through the civil war in Northern Sumatra (Aceh), unrest in Riau and South Thailand as well as widespread piracy. The growth potential is enormous and is partly realized in the SIJORI growth triangle of Singapore, Johore (Malaysia) and Riau (Indonesia); in the industrial growth of the Western part of Malaysia bordering the Straits; the industrial area around Penang (Malaysia) and the international tourism development on the islands of Langkawi (Malaysia) and Phuket (Thailand).
urn:nbn:de:0202-20080911173
Keywords: 330